Transmisi dan Transformasi Praktik Pembacaan Al-Qur’an dalam Komunitas Muslim Indonesia: Studi Kasus pada Jamaah Masjid Miftahul Huda Domerto Munjungan Trenggalek Jawa Timur - Habibah, Umi Nur; Ahmad Zainal Abidin (Nun: Jurnal Studi Alquran dan Tafsir di Nusantara, 2023)
This article examines the practice of reciting surah al-Insyirah and surah al-Ikhlas of the congregation of the Miftahul Huda Mosque Domerto Munjungan Trenggalek, East Java. The focus of this article is to examine the reception of the Qur'an in the recitation of surah al-Insyirah and surah al-Ikhlas of the congregation of the Miftahul Huda Mosque Domerto Munjungan, Trenggalek, East Java. The formulation of the problem in this study is, 1) how is the ritual of reading surah al-Insyirah and surah al-Ikhlas, 2) how is the meaning of the congregation according to the sociological theory of knowledge of Karl Mannheim, 3) how is its transmission and transformation. This article is a field study using a qualitative descriptive method. The tools used for data collection are interviews with 12 people, observations carried out 4 times and a literature review. This article also uses Karl Mannheim's theory of sociology of knowledge. After the researchers conducted the research, it can be concluded that the congregation of the Miftahul Huda Mosque Domerto Munjungan Trenggalek routinely performs the practice of reciting surah al-Insyirah and surah al-Ikhlas. First, this reading is done every Monday night after the congregational Isha' prayer. Second, the meaning contained is divided into 3 meanings, the first meaning is the objective meaning where in this meaning the Miftahul Huda mosque congregation understands the practice of reading Surah al-Insyirah and Surah al-Ikhlas as routine activities carried out every Monday night. The second meaning is expressive meaning that can be seen from the congregation's response to the practice of reciting surah al-Insyirah and surah al-Ikhlas as a means of friendship between others, a form of connecting ties of brotherhood, as a means of increasing devotion to Allah, and is believed to be able to carry out all their affairs. . The last meaning is the documentary meaning which can be seen that this practice is a culture that is ingrained and cannot be released for the congregation. Third, the process of transmission and transformation can be seen from several hadiths that explain it. The transmission process of surah al-Insyirah and surah al-Ikhlas can be known through hadith narrations. In the transmission of surah al-Insyirah, the author finds the book of maraqil ubudiyah and the book of khazinat al-Asrar. While the transmission of Surah al-Ikhlas comes from the hadith of 'Aisyah ra about the habits of the Prophet Muhammad before sleeping. The transformation can be seen from the changes during the time of the Prophet Muhammad, becoming a practice that is carried out every Monday night after the Isha prayer by the congregation of the Miftahul Huda Mosque Domerto Munjungan Trenggalek.